Effects of fenofibrate on inflammatory cytokines in diabetic retinopathy patients. Issue 31 (August 2017) - Ju, Hai-Bing; Zhang, Fu-Xian; Wang, Shuang; Song, Jie; Cui, Tao; Li, Li-Feng; Zhang, Hai-Yan
Abstract : Abstract: The role of cytokines in diabetic retinopathy (DR) and effects of fenofibrate on cytokines were explored by observing changes in serum IL-1β, TNF-α, VEGF, and Lp-PLA2 in different stages of DR and the intervention effect of oral fenofibrate on cytokines. In total, 190 patients with type 2 DR were enrolled and divided into 3 groups: diabetic without retinopathy (NDR) group (n = 30), nonproliferative diabetic retinopathy (NPDR) group (n = 80), and proliferative diabetic retinopathy (PDR) group (n = 80). According to whether or not to accept fenofibrate treatment, NPDR and PDR groups were further divided into the NPDR control (NPDR1) group (n = 40) and the NPDR treatment (NPDR2) group (n = 40), and the proliferative diabetic retinopathy control (PDR1, n = 40) group and the proliferative diabetic retinopathy treatment (PDR2) group (n = 40). At 12 weeks after fenofibrate treatment, serum IL-1β, TNF-α, VEGF, and Lp-PLA2 levels were detected. In PDR and NPDR patients, levels of serum cytokines such as IL-1β (120.56 ± 27.32 pg/mL vs 112.34 ± 19.45 pg/mL vs 82.9 ± 13.8 pg/mL), TNF-α (125.86 ± 25.57 pg/mL vs 109.48 ± 20.15 pg/mL vs 80.7 ± 12.8 pg/mL), VEGF (166.65 ± 37.74 pg/mL vs 148.54 ± 36.27 pg/mL vs 88.97 ± 24.86 pg/mL), and Lp-PLA2 (172.34 ± 45.22 μg/L vs 154.66 ± 40.98 μg/L vs 125.88 ± 38.87 μg/L) were significantly higher than in diabetes patients without retinopathy. After fenofibrate treatment, serum IL-1β, TNF-α, VEGF, and Lp-PLA2 significantly decreased in NPDR and PDR patients. Serum IL-1β, TNF-α, VEGF, and Lp-PLA2 play an important role in occurrence and development of diabetic retinopathy. Fenofibrate can reduce cytokine levels in DR patients and improve inflammatory response.